MIMOG (Mastering of Islamic Monopoly Grammar) As a Media in Teaching Writing - Ariansyah, Muchammad Ravli; Syafi’i, Ahmad (Efektor, 2018)
Writing is the difficult skill in learning English. Hence, this article talks about a media for teaching writing. To make students get the idea in writing easily the teacher should be creative and innovative. The media of MIMOG (Mastering of Islamic Monopoly Grammar) will become one of an innovative media to be influence in students’ writing skill. The subject of using this media is the students of high school. The media indicates that students will understand how to write with appropriate tenses. A good design of the media is also influence in student’s interest. Besides that, MIMOG media will give the Islamic Integration in the process of game. So, not only the students’ writing skill will improve but also the students’ character.